2012
DOI: 10.1016/j.irfa.2011.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Cointegration relationship and time varying co-movements among Indian and Asian developed stock markets

Abstract: This paper aims to explore links between the Indian stock market and three developed Asian markets (i.e. Hong Kong, Japan and Singapore). The index prices are non-stationary so we used cointegration methodologies in order to explore interdependencies. Johansen methodologies reject the hypothesis of long-run relationships among all stock markets, while the Gregory-Hansen test rejects the hypothesis of no cointegration with structural breaks. Our results suggest that in the longterm the benefits for investing in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
66
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(73 citation statements)
references
References 57 publications
6
66
1
Order By: Relevance
“…However, our findings extends their results by showing that the contagion effect exists between the United State and Hong Kong and Singapore during the subprime crisis. In addition, our results are consistent with a study by Gupta and Guidi (2012) who find evidence of contagion effect from the United States to the equity market of India, as well as a study by Syllignakis and Kouretas (2011) who provide evidence of the transmission of the shock in the United States to the CEE stock returns during the 2007-2009 financial crises.…”
Section: Dynamic Conditional Correlationsupporting
confidence: 92%
“…However, our findings extends their results by showing that the contagion effect exists between the United State and Hong Kong and Singapore during the subprime crisis. In addition, our results are consistent with a study by Gupta and Guidi (2012) who find evidence of contagion effect from the United States to the equity market of India, as well as a study by Syllignakis and Kouretas (2011) who provide evidence of the transmission of the shock in the United States to the CEE stock returns during the 2007-2009 financial crises.…”
Section: Dynamic Conditional Correlationsupporting
confidence: 92%
“…The different impact of the same factor on different stock markets indicates the asymmetric response of the stock market to macroeconomic shocks. On similar grounds, a study by Gupta and Guidi (2012) on the links between the Indian stock market and developed Asian markets (Hong Kong, Japan and Singapore) found that there is a short-run relationship and absence of a strong long-run relationship among these markets. Moreover, in a recent endeavor, Nashier (2015) found elements of association between BRICS 3 and UK and US stock markets in the period from 2004-2013, although they did not look at any structural break in the relationship due to financial crises and looked at the association as a whole which might be different in the Post-GFC (2008) world.…”
Section: Introductionmentioning
confidence: 94%
“…From a methodological point of view, the empirical literature has proposed different measurement frameworks relying on price-based indicators: Vector Auto-Regression (VAR) models (Khalid and Kawai, 2003;Elyasiani and Wanli, 2008;Jayasuriya, 2011), standard cross-country correlation (Watson, 1980;Meric and Meric, 1989;Goetzmann et al, 2005), cointegration and error-correction models (Laopodis, 2011;Gupta and Guidi, 2012), GARCH models (Kim et al, 2006;Carrieri et al, 2007;Wang and Moore, 2008;Egert and Kocenda, 2011), asset pricing models (Nellis, 1982;Mauro et al, 2002;de Jong and de Roon, 2005;Barr and Priestley, 2004;Abad et al, 2010;Volosovych, 2011;Donadelli and Paradiso, 2014), and common component approach (Carrieri et al, 2007;Pukthuanthong and Roll, 2009;Yu et al, 2010). VAR-based studies make use of impulse response analysis to investigate the effects of contagion and the degree of interdependence, whereas cointegration-based studies aim to assess the presence of a long-run equilibrium among cross-country financial variables, such as stock or bond prices.…”
Section: Introductionmentioning
confidence: 99%